Interconnected living in a quarter for persons with dementia. (2nd July 2020) - Gerka, A.; Eichelberg, M.; Stolle, C.; Tietjen-Müller, C.; Brinkmann-Gerdes, S.; Hein, A.
ABSTRACT: Objective: In this work, we propose a new care concept for dementia patients in their own apartments: interconnected living in a quarter. We describe a technical setup that is comprised of a safety system and an activity detection system. The latter detects, processes and illustrates activities of daily living to help the quarter managers to provide appropriate interventions for persons with dementia in the quarter. Participants: The nine-month field study reported in this work was conducted in two quarters with eight participants. Methods: We evaluated different possibilities to determine activity indicators with the aim of providing information that enables the quarter managers to offer exactly the level of support needed by each individual patient. To evaluate the usefulness and the perception of the technical infrastructure, qualitative interviews with the dementia patients and the quarter managers were conducted. Results: The results indicate that the interconnected living concept helps to increase the safety of the dementia patients. Additionally, several activity indicators that help the quarter managers to offer the appropriate level of support to the dementia patients have been identified. Conclusion: The presented concept, which has been evaluated in a real-world-setting, constitutes a new holistic and cross-disciplinary dementia care approach.